The intrinsically disordered N‐terminal region of mouse DNA polymerase alpha mediates its interaction with POT1a/b at telomeres. (12th April 2021) - Mizuno, Takeshi; Hirabayashi, Kei; Miyazawa, Sae; Kobayashi, Yurika; Shoji, Kenta; Kobayashi, Masakazu; Hanaoka, Fumio; Imamoto, Naoko; Torigoe, Hidetaka
Abstract: Mouse telomerase and the DNA polymerase alpha‐primase complex elongate the leading and lagging strands of telomeres, respectively. To elucidate the molecular mechanism of lagging strand synthesis, we investigated the interaction between DNA polymerase alpha and two paralogs of the mouse POT1 telomere‐binding protein (POT1a and POT1b). Yeast two‐hybrid analysis and a glutathione S‐transferase pull‐down assay indicated that the C‐terminal region of POT1a/b binds to the intrinsically disordered N‐terminal region of p180, the catalytic subunit of mouse DNA polymerase alpha. Subcellular distribution analyses showed that although POT1a, POT1b, and TPP1 were localized to the cytoplasm, POT1a‐TPP1 and POT1b‐TPP1 coexpressed with TIN2 localized to the nucleus in a TIN2 dose‐dependent manner. Coimmunoprecipitation and cell cycle synchronization experiments indicated that POT1b‐TPP1‐TIN2 was more strongly associated with p180 than POT1a‐TPP1‐TIN2, and this complex accumulated during the S phase. Fluorescence in situ hybridization and proximity ligation assays showed that POT1a and POT1b interacted with p180 and TIN2 on telomeric chromatin. Based on the present study and a previous study, we propose a model in which POT1a/b‐TPP1‐TIN2 translocates into the nucleus in a TIN2 dose‐dependent manner to target the telomere, where POT1a/b interacts with DNA polymerase alpha for recruitment at the telomere for lagging strand synthesis. Abstract : POT1a/b‐TPP1‐TIN2 translocates into the nucleus in a TIN2‐dose dependent manner to target the telomere, where POT1a/b interacts with DNA polymerase alpha for recruitment at the telomere for lagging strand synthesis.